Sprawozdanie z badań jakościowych prowadzonych na zlecenie CODN w klasach dwujęzycznych z językiem hiszpańskim w polskich gimnazjach i liceach - Majewska, Renata; Tatoj, Cecylia (Neofilolog, 2019)
The paper presents the results of a qualitative study, contained in the evaluative report prepared in 2008 and commissioned by the National In-service Teacher Training Centre [Centralny Ośrodek Doskonalenia Nauczycieli, CODN]), conducted in bilingual classes with Spanish as a second language in Polish junior high schools and high schools. This report highlights the basic features of these classes in which Spanish is taught as a second language, discusses the basic needs, gives an outline of future recommendations as well as proposes some fundamental changes.